ANALYSIS OF THE ROLE OF THE USE OF DANA APPLICATIONS IN COFFEE SHOP CORNER OF ANGKRINGAN, EAST MEDAN DISTRICT - Zulfikar, Muhammad Rofi; Afif, M. Naufal; Aushaf Assegaf, M. Naufal; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to examine the role of using the Dana application as a means of payment in UMKMs Angular Angkringan in East Medan, North Sumatra. The approach used in this study uses a Qualitative Approach. Data collection was carried out by interviewing business owners, namely the owner and 2 staff. Based on the results of the study, it is known that this business problem is that the level of use of the Dana application in the UMKM business is in the high-level category. Business people also make it easier for business owners because of time efficiency. Meanwhile, consumers get benefits in the form of promos offered by business owners and the Dana application. This is certainly very beneficial for business people in doing all transaction matters.